Examining building-related symptoms in clinical practice - Andersson, Kjell (SJWEH Supplements, 2008)
Evaluating relationships between indoor-climate factors and building-related symptoms is difficult due to the nonspecificity of symptoms and the complexity of exposures, both physical and psychosocial in character. At the group level, these problems can be handled efficiently by occupational health personnel using a stringent strategy and involving multiprofessional teams. However, at the individual level, the difficulties are even greater, mainly due to the differences in sensitivity and vulnerability among people and a lack of knowledge about which medical and psychosocial mechanisms are involved. Over the last few decades, some new clinical instruments and methods have been introduced to register subtle objective effects, and they will also, hopefully, increase the possibilities for making better evidence-based assessments in the future at the individual level. There is an urgent need for more basic research about the medical and neuropsychological mechanisms involved.
Keywords: building; building-related symptom; clinical practice; examination; objective measure; occupational health care; questionnaire; sick building; sick-building syndrome; strategy; symptom